2018
DOI: 10.1096/fj.201701326r
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of the purinergic signaling system exhibit diverse effects on the degeneration of valvular interstitial cells in a 3‐D microenvironment

Abstract: Calcific aortic valve disease is an active disease process with lipoprotein deposition, chronic inflammation, and progressive leaflet degeneration. Expression of ectonucleotidases, a group of membrane-bound enzymes that regulate the metabolism of ATP and its metabolites, may coregulate the degeneration process of valvular interstitial cells (VICs). The aim of this study was to investigate the role of the enzymes of the purinergic system in the degeneration process of VICs. Ovine VICs were cultivated in vitro u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[10] Adenosine was also attributed to have pro-stenotic properties by the stimulation of ovine VIC degeneration by A2aR and A2b receptor (A2bR) activation. [66] On the contrary, treatment with A2bR agonist significantly reduced the calcification volume of progenitor cell-derived teratomas from patients with CD73 deficiency. [65] Also in our recent work, we have shown that CD73−/− mice spontaneously developed aortic valve dysfunction increasing peak aortic flow and valvular Fig.…”
Section: Discussionmentioning
confidence: 97%
“…[10] Adenosine was also attributed to have pro-stenotic properties by the stimulation of ovine VIC degeneration by A2aR and A2b receptor (A2bR) activation. [66] On the contrary, treatment with A2bR agonist significantly reduced the calcification volume of progenitor cell-derived teratomas from patients with CD73 deficiency. [65] Also in our recent work, we have shown that CD73−/− mice spontaneously developed aortic valve dysfunction increasing peak aortic flow and valvular Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Further, there is a lot of literature, to which current results and outcome measures can be compared [ 26 , 41 , 42 ]. Artificially created 3D environments of VICs are more physiologically relevant and predictive than 2D cultures and exhibit a higher degree of structural complexity and homeostasis but are time consuming, labor intensive, and expensive [ 27 , 33 , 41 , 42 ]. Furthermore, 3D cultures created from specific tissues (e.g., basement membrane extracts) can contain undesirable components such as viruses or growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 3D cultures created from specific tissues (e.g., basement membrane extracts) can contain undesirable components such as viruses or growth factors. It also must be mentioned that the microscopical analysis of 3D cultures is accompanied by technical challenges, while 2D cultures can be analyzed by almost any kind of imaging [ 27 , 33 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian heart built of cardiomyocytes also contains a large population of non-myocyte cells (e.g., interstitial cells, endothelial cells) [12,13]. Recently, VICs have been discussed in the literature as important players in the degeneration of the heart valves, participating in the pathogenesis of CAVD [11,[14][15][16]. These double-faced cells seem to be crucial in homeostasis regulation but, on the other hand, are responsible for aortic valve fibrosis and osteogenic degeneration, which is associated with activation of developmental transcriptional regulatory pathways [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%